Permohonan Itsbat Nikah Untuk Perkawinan Kedua oleh Istri yang Bercerai di Luar Pengadilan Agama (Studi Kasus Padang Pariaman) - Fauza, Nurul; Yaswirman, Yaswirman; Najmi, Najmi (Universitas Batanghari Jambi, 2024)
Divorces outside the court often occur, resulting in the marriage status remaining valid according to Indonesian positive law. This leads couples who wish to remarry to do so clandestinely and seek marital validation through the religious court. Therefore, the purpose of this research is to understand the process of resolving itsbat nikah petitions for second marriages by wives who divorced outside the court and the legal consequences for the parties from the rejection of itsbat nikah by the religious court. This research employs an empirical juridical method focusing on field realities related to applicable legal aspects. Data analysis is conducted qualitatively to depict the research subjects and objects, with theories developed from the acquired data. The research findings indicate that the itsbat nikah process begins with a petition to the pusbakum, revealing that the couple were single before their secret marriage in 2007. However, during the trial, it was revealed that the wife had legally married in the Office of Religious Affairs (KUA) in 2004 and divorced outside the court in the same year, resulting in the rejection of the itsbat nikah petition. Consequently, the wife's post-divorce iddah maintenance rights are lost, but the child's legal status remains recognized, in accordance with Constitutional Court Decision No. 46/PUU-VII/2010.